2023
DOI: 10.1021/acsami.3c12602
|View full text |Cite
|
Sign up to set email alerts
|

Modulating Barrier Properties of Stereocomplex Polylactide: The Polymorphism Mechanism and Its Relationship with Rigid Amorphous Fraction

Qi Chen,
Rafael Auras,
Jacob Judas Kain Kirkensgaard
et al.

Abstract: The barrier properties of semicrystalline polymers are crucial for their performance and their use as packaging materials. This work uncovers the mechanism of polymorphism modification (α, α′ and stereocomplex-crystals) and its combined effect on the oxygen and water vapor barrier properties of semicrystalline stereocomplex polylactide (SCPLA). A polymorphic selective filler-type nucleator was employed to eliminate the temperature effect on the development of polymorphism and rigid amorphous fraction (RAF), al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Chen et al reported similar findings on SC-PLA and the distribution between the formation of α-crystals and SC-crystals; they reported that at 140 °C, the α-crystals formed in a much higher abundance than SC-crystals. 41 This study was conducted at 160 °C but yielded similar findings, which means the overall X C improves the barrier more than the individual X HC or X SC formed. Additional studies could be conducted to decouple the role of the α-crystals and the SC-crystals.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Chen et al reported similar findings on SC-PLA and the distribution between the formation of α-crystals and SC-crystals; they reported that at 140 °C, the α-crystals formed in a much higher abundance than SC-crystals. 41 This study was conducted at 160 °C but yielded similar findings, which means the overall X C improves the barrier more than the individual X HC or X SC formed. Additional studies could be conducted to decouple the role of the α-crystals and the SC-crystals.…”
Section: Resultsmentioning
confidence: 57%
“…The peaks at 2 θ = 12.0, 20.8, and 24.1 correspond to the SC-crystal. 41,47 As shown in Fig. 5, the α-crystal dominates in all the blends except the 50/50 PLLA/PDLA blend.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation